Wind turbines as a metamaterial-like urban layer: an experimental investigation using a dense seismic array and complementary sensing technologies - Pilz, Marco; Roux, Philippe; Mohammed, Shoaib Ayjaz; Garcia, Raphael F.; Steinmann, Rene; Aubert, Coralie; Bernauer, Felix; Guéguen, Philippe; Ohrnberger, Matthias; Cotton, Fabrice (Frontiers in Earth Science, 2024)
The deflection and the control of the effects of the complex urban seismic wavefield on the built environment is a major challenge in earthquake engineering. The interactions between the soil and the structures and between the structures strongly modify the lateral variability of ground motion seen in connection to earthquake damage. Here we investigate the idea that flexural and compressional resonances of tall turbines in a wind farm strongly influence the propagation of the seismic wavefield. A large-scale geophysical experiment demonstrates that surface waves are strongly damped in several distinct frequency bands when interacting at the resonances of a set of wind turbines. The ground-anchored arrangement of these turbines produces unusual amplitude and phase patterns in the observed seismic wavefield, in the intensity ratio between stations inside and outside the wind farm and in surface wave polarization while there is no metamaterial-like complete extinction of the wavefield. This demonstration is done by setting up a dense grid of 400 geophones and another set of radial broadband stations outside the wind farm to study the properties of the seismic wavefield propagating through the wind farm. Additional geophysical equipment (e.g. an optical fiber, rotational and barometric sensors) was used to provide essential explanatory and complementary measurements. A numerical model of the turbine also confirms the mechanical resonances that are responsible for the strong coupling between the wind turbines and the seismic wavefield observed in certain frequency ranges of engineering interest.